Letters to a Young Conservative. - D'Souza, Dinesh (Letters to a Young ..., 2009)
Dinesh D'Souza rose to national prominence as one of the founders of the Dartmouth Review, a leading voice in the rebirth of conservative politics on college campuses in the 1980s. He fired the first popular shot against political correctness with his best.